Shaping Healthy Eating Habits in Children With Persuasive Strategies: Toward a Typology - Alice Binder; Brigitte Naderer; Jörg Matthes (Frontiers Media S.A., 2021)
There is an abundance of evidence that the presentation of unhealthy foods (UHFs) in different media has the power to shape eating habits in children. Compared to this rich body of work with regard to the effects of UHF presentations, studies testing the effects of healthy foods (HFs) are less conclusive. In particular, while the persuasive mechanisms behind HF presentations are well-understood, we lack insights about the role of messages factors, that is, how are (and should) HFs (be) presented in order to foster healthy eating habits in children. This paper tackles this research gap by suggesting the Persuasive Strategies Presenting Healthy Foods to Children (PSPHF) typology, classified along three pillars: (a) composition-related characteristics, (b) source-related characteristics, and (c) information-related characteristics. Against the background of the PSPHF typology, we review the available empirical evidence, outline pressing research gaps, and discuss implications for researchers, health promoters, and program planers.